Kearifan Lokal Dalam Kitab Tafsir: Telaah Tafsir Al-Iklil Fi Ma’ani Al-Tanzil Karya Misbah Mustofa Terhadap Tradisi Jawa Di Indonesia - Elok Atika (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study analyses Misbah Mustafa's Tafsir Al-Iklil Fi Ma'ani Al-Tanzil, a tafsir of the Qur'an in Javanese with pegon script, to understand its role in contextualising Islamic teachings in Javanese socio-cultural dynamics. This study answers how vernacularisation through local language and script bridges the understanding of the Qur'an while criticising Javanese traditions such as tahlilan, grave pilgrimage, and celametan. Using a qualitative analytical method and a historical-sociological approach, the research focuses on Misbah's interpretive method, which is influenced by his pesantren education, modernist thinkers, and studies in the Middle East. The results show that Misbah combines classical tafsir with the local context, providing constructive criticism rather than absolute rejection of Hindu-Buddhist traditions. The use of Javanese language and Pegon script not only increases accessibility for non-Arabic people, but also reflects Javanese socio-religious identity. An example of the interaction of sacred texts with local culture, contributing to the development of Qur'anic studies in Indonesia and strengthening the adaptation of Islam in the archipelago, this study confirms vernacularisation as a key strategy in maintaining religious authenticity by responding to cultural realities.